2007
DOI: 10.1080/15412550701595716
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anxiety and Depression in Patients with Severe COPD: Similar High Levels with and without LTOT

Abstract: The benefits of long-term oxygen therapy (LTOT) on mood in Chronic Obstructive Pulmonary Disease (COPD) are unproven. Longitudinal studies are affected by disease progression, the increased package of care (with LTOT) and may not control for known confounders on mood. We compared the point prevalence and severity of mood disturbance in patients with severe COPD, not on LTOT (the -LTOT group) to those with COPD on LTOT (the +LTOT group). We mailed the Hospital Anxiety and Depression (HAD) Score to 182 consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 23 publications
2
27
2
Order By: Relevance
“…COPD patients often have psychological disorders, including depression, and such patients tend to have more frequent exacerbations and a poor prognosis [3-7]. Recently, we demonstrated that depressed COPD patients had a lower HRQOL and more frequent exacerbations and hospitalizations those non-depressed COPD patients [3].…”
Section: Introductionmentioning
confidence: 99%
“…COPD patients often have psychological disorders, including depression, and such patients tend to have more frequent exacerbations and a poor prognosis [3-7]. Recently, we demonstrated that depressed COPD patients had a lower HRQOL and more frequent exacerbations and hospitalizations those non-depressed COPD patients [3].…”
Section: Introductionmentioning
confidence: 99%
“…Difficulty in falling asleep may be a predictor for the development of depression in elderly people, including patients with COPD 7 . Patients with more severe COPD have a higher incidence of psychological disorders 10,11 . There is increasing evidence that psychological disorders may have a direct impact on HRQOL and the frequency of exacerbations and hospitalizations in patients with COPD 10–14 .…”
Section: Introductionmentioning
confidence: 99%
“…7 Patients with more severe COPD have a higher incidence of psychological disorders. 10,11 There is increasing evidence that psychological disorders may have a direct impact on HRQOL and the frequency of exacerbations and hospitalizations in patients with COPD. [10][11][12][13][14] Depression and sleep disorders may affect exacerbations, hospitalizations and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies investigating the relation between COPD and depression in COPD patients with stable mild or moderate disease (van Ede et al, 1999;van Manen et al, 2002). However, few studies involving severe COPD have been reported (Kim et al, 2014;Lacasse, Rousseau, & Maltais, 2001;Lewis et al, 2007). Many studies focused on "depressive symptoms" rather than depression as a whole, while examining the relation between depression and COPD (Stage, Middelboe, Stage, & Sorensen, 2006).…”
mentioning
confidence: 99%